2014
DOI: 10.1212/wnl.0000000000000713
|View full text |Cite
|
Sign up to set email alerts
|

JCV GCN in a natalizumab-treated MS patient is associated with mutations of the VP1 capsid gene

Abstract: JCV GCN should be considered in patients on natalizumab presenting with progressive cerebellar symptoms and cerebellar atrophy, and is associated with mutations in the JCV VP1 gene. Natalizumab withdrawal may be complicated by JCV GCN IRIS, and require treatment with corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
3
32
0
4
Order By: Relevance
“…JCV affects the neurons in the cerebellum when there is a mutation of the VP1 gene coding for the major capsid protein, which changes the viral tropism from glial cells to cerebellar granule cells. 2,4,10,14 This clinical syndrome is called granule cell neuronopathy, and the clinical manifestations include balance instability and impaired coordination with or without slurring of speech or abnormal eye movements. This atypical presentation can be diagnostically challenging, delaying testing for JCV-associated disease and the initiation of immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JCV affects the neurons in the cerebellum when there is a mutation of the VP1 gene coding for the major capsid protein, which changes the viral tropism from glial cells to cerebellar granule cells. 2,4,10,14 This clinical syndrome is called granule cell neuronopathy, and the clinical manifestations include balance instability and impaired coordination with or without slurring of speech or abnormal eye movements. This atypical presentation can be diagnostically challenging, delaying testing for JCV-associated disease and the initiation of immune reconstitution.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our patients, there have been documented cases of granule cell neuronopathy in patients on long-term rituximab as well as natalizumab therapy. 2,10,14 A second diagnostic challenge was the 25% failure rate of CSF PCR testing among patients with JCV. Studies have demonstrated that the sensitivity of first-generation PCR detection for JCV DNA in CSF ranges from 75% to 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Adding our 5 cases leads to a total of 23 reported cases (22 probable and 1 possible). Most cases of JC-GCN were described in HIV-infected patients [15][16][17], but some others were in patients with sarcoidosis [18], congenital CD40 ligand deficiency [19] and rituximab treatment [20] or natalizumab treatment for multiple sclerosis [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…On sequencing viral DNA in a later study on the same brain samples [27], Dang and Koralnik showed a deletion in the C-terminal portion of the VP1 gene, which encodes for the major capsid protein. Other mutations have been described in other patients, in the VP1 gene [11,20,22] or in the regulatory region [12], and several strains of JCV can be found in the same patient [20,2]. The different alleles are thought to change the receptor specificity of the virus for different peripheral cells.…”
Section: Discussionmentioning
confidence: 99%
“…JCV-GCN kan forekomme isolert eller i kombinasjon med PML. Det er rapportert svaert sjeldne tilfeller av JCV-GCN hos pasienter som får behandling med natalizumab (Agnihotri, 2014;Schippling, 2013 Påvisning av JCV-DNA i CSF ved bruk av PCR (polymerase chain reaction) er en sterk bekreftelse av diagnosen, fordi den har en sensitivitet på 72-100 % og en spesifisitet på 92-100 % (Cinque et al, 1997). Dersom CSF-PCR er negativ, anbefales det at CSF-PCR gjentas.…”
Section: Patologiunclassified